Dapatkah Kepemilikan Institusional Memoderasi Pengaruh Perencanaan Pajak Terhadap Kualitas Laba? - Christabelle, Angelica; Trisnawati, Estralita; Firmansyah, Amrie (E-Jurnal Akuntansi, 2022)
This study aims to obtain empirical evidence regarding the effect of managerial ownership, tax planning, and information asymmetry on earnings quality with institutional ownership as a moderating variable in Property and Real estate Companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used was purposive sampling method. The company sample is 13 companies with 3 years of observation, then 39 observations are obtained. The data analysis technique used multiple regression for panel data. The results show that managerial ownership has a positive effect on earnings quality and institutional ownership is able to moderate the effect of managerial ownership and tax planning on earnings quality. This research indicates that the tax authorities in Indonesia should update and improve the existing system so that they can better monitor the actions of taxpayers. Keywords: Managerial Ownership; Tax Planning; Institutional Ownership; Earnings Quality.